Accuracy of diagnoses of skin diseases in a pediatric emergency room: A retrospective study - Suzan A AlKhater (Wolters Kluwer Medknow Publications, 2020)
Background: Cutaneous disorders are common in children. Few studies have assessed the diagnostic accuracy of pediatricians in diagnosing skin disorders. Purpose: In this study, the accuracy of the diagnoses of skin diseases made in a pediatric emergency room (ER) was determined. Methods: Data were obtained from a retrospective study of children with dermatological disorders seeking emergency services in the pediatric ER in a teaching hospital in Saudi Arabia. Descriptive statistics were used to determine the distribution of patients and time characteristics. Crude and adjusted logistic regression models, controlling for demographic and time-associated characteristics, were used to determine the association between clinical and other characteristics and diagnostic accuracy of pediatricians. Results: There were statistically significant differences in the overall distribution of the study population by gender, season, time of week, shift, and referrals (P < 0.05). After adjusting for these factors, every unit increase in age (years) was associated with a 38% increase (odds ratio: 1.38; 95% confidence interval: 1.18-1.61) in the odds of pediatricians being likely to have the correct diagnosis. There were significant differences between the diagnosis made by pediatrician and the final diagnoses made by senior staff (P < 0.001). Infections and neonatal skin diseases were underdiagnosed, while overdiagnoses of allergic and hypersensitivity reactions were observed. Conclusion: The results emphasize the importance of orienting pediatric trainees on the dermatological aspects of diseases, particularly on the topics involving infectious, allergic and hypersensitivity reactions, and neonatal skin disorders. This points out the importance of making dermatology rotation as a core requirement during the residency training rather than just optional electives.